PENGINJILAN YANG DIBERDAYAKAN: NUBUATAN YOEL MENGENAI ERA PENCURAHAN ROH KUDUS - Leonardo Latumanuwy; Gernaida Krisna R. Pakpahan (Diegesis : Jurnal Teologi, 2022)
The outpouring of the Holy Spirit is often associated with the words of the apostle Peter when quoting the words of Joel. 2:28-29 contains God's promise to all mankind. Fulfillment of this promise aims to empower God's people in carrying out God's mission, namely evangelism. Nevertheless, ironically the congregation does not necessarily understand the meaning of this text and is reluctant to preach the gospel. This study seeks to find the meaning of the text with the message of the gospel. The method used is a qualitative narrative with hermeneutic procedures. This study finds the meaning of the text that the outpouring of the Holy Spirit for every believer without any limitations with the aim of evangelism empowered by the Holy Spirit so that all nations can know the great work of God done through Jesus Christ. This study also recommends that the church understand the outpouring of the Holy Spirit, empowered evangelism, and synergies of evangelism programs between churches.